Home literacy practices: do fathers play their parts? - Wahiza Wahi; Hazita Azman (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
Much has been written about the significance of parents’ involvement in the growth of children’s literacy at home and the correlation between their literacy practices and academic achievement at school. While most literature has focused on mothers’ contribution alone in their children’s literacy development, the involvement of fathers as the most important figures in the domestic site has been given less attention. Informed by theories of literacy as a social practice, this paper reports the findings of a close examination on the literacy practices of Malay fathers and their roles and contributions to their children’s literacy development. Employing a qualitative case study approach, this paper draws on data gathered from in-depth interviews with the participants and supplemented by observations at the participants’ residences. Key findings centre on the fathers’ distinctive values and ways of sustaining literacy for their children. The findings also call attention to the predominant influence of membership of diverse social communities on the fathers’ literacy practices.